Hur kopplad är asp till tidigare jordbruksmark? : en studie av aspförekomst och tidigare markanvändning i fem län i Mellansverige - Dahl, Jenny (SLU/Dept. of Ecology, 2013)
Aspen (Populus tremula) is a tree that is important for biodiversity. It is a pioneer tree that is favored by much light. It is possible that aspens that regenerated on agricultural land have a different importance for biodiversity than aspens that regenerated in forests, since their conditions have been different. By studying how the land use have changed you can see how many of today’s aspens regeneretad on agricultural land. This paper studies three questions and includes five regions (Stockholm, Uppsala, Västmanland, Örebro and Värmland):